Accuracy of peplicating static torque and its effect on shooting accuracy in young basketball players - Struzik, A.; Rokita, A.; Pietraszewski, B.; Popowczak, M. (Human Movement, 2014)
Accurate shooting in basketball is a prerequisite for success. Coordination ability, one of the abilities that determine the repeatability of accurate shooting, is based on kinesthetic differentiation. The aim of the study was to evaluate the strength component of kinesthetic differentiation ability and determine its relationship with shooting accuracy. Methods. Peak muscle torque of the elbow extensors under static conditions was measured in 12 young basketball players. Participants then reproduced the same movement at a perceived magnitude of 25%, 50%, and 75% of static peak torque, with error scores calculated as a measure of kinesthetic differentiation. The results were compared with players` field goal percentages calculated during game play in a regional championship. Results. No statistically significant relationships were found between the level of kinesthetic differentiation ability and field goal percentage. Additionally, no upper limb asymmetry was found in the sample. Conclusions. The relatively high levels of elbow static peak torque suggest the importance of upper limb strength in contemporary basketball. The lack of a statistically significant difference between the right and left limbs decreases the risk of suffering injury. It is likely that choosing other suitable tests would demonstrate the relationships between field goal percentage and kinesthetic differentiation ability.